(untitled) (Journal of Psychiatrists’ Association of Nepal, 2017)
Trichotillomania once was considered as a rare disorder but now it is recognized as a psychiatric illness that is not as rare as previously thought. Standard treatment guideline of this disorder, especially for children is not available till the present date. In this report, a case of childhood trichotillomania, its various diagnostic possibilities and successful treatment with Risperidone in a child has been described.